Effect of Packaging and Temperature on Survival Kinetics of Campylobacter jejuni on Precooked Chicken Breast. Issue 4 (12th September 2014) - Park, Na Yoon; Ro, Eun Young; Jo, Hye Jin; Park, Kun Sang; Yoon, Ki Sun
Abstract The survival ability of Campylobacter jejuni in poultry has been a major public health risk because of the low infectious dose. The objective of this study was to investigate the effects of different packaging condition and temperature on the survival kinetics of C. jejuni ATCC 33291 on precooked chicken breast. Survival kinetics of C. jejuni were also compared with those of C. coli ATCC 43486. Inoculated chicken breasts with 5.0–6.0 log cfu/g were packed in three different ways (aerobic, semi‐aerobic or vacuum), which were stored at 4, 10, 17, 24, 30 and 36C. Survival curves were fitted to Baranyi model to obtain the values of lag time and death rate of C. jejuni. During storage, the greatest reduction of C. jejuni (4.316 log cfu/g) was observed in aerobic packaged chicken breast at 24C, while the least reduction of C. jejuni (1.031 log cfu/g) was observed in vacuum‐packaged chicken breast at 4C. Lag time was affected by packing method, temperature and strain. Similar survival behavior of C. coli to C. jejuni was observed only at 10C. At the temperatures above 24C, lag phase of C. jejuni was only observed in semi‐aerobic or vacuum‐packed chicken breasts, indicating that C. jejuni survived better than C. coli, for which no lag phase was observed. The results indicated that vacuum or semi‐aerobic packaging on poultry product at 4C, which is the most popular method at retail markets, created the highest risk for C. jejuni survival. Practical Applications Survival ability and pattern of Campylobacter in poultry product at retail market is affected by packing condition, storage temperature and species. The survival model for C. jejuni ATCC 33291 in precooked chicken was not suitable for use in making predictions for C. coli. ATCC 43486, thus the survival model for C. coli must be developed separately. The viable count of C. jejuni in tailing part in survival curve can be very dangerous, thus, preventing cross contamination and proper cooking must be reemphasized in the food service establishments and at home.